2016
DOI: 10.1016/j.ijgo.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Area under curve of temporal estradiol measurements for prediction of the detrimental effect of estrogen exposure on implantation

Abstract: The area under the curve of estradiol measurements during ART cycles might be useful for predicting failure of implantation and clinical pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…This was observed in several studies, who found the lower implantation rate in high estradiol level condition during IVF ET cycle [10] [14] [15]. However, the difference in pregnancy results was not the primary goal of this study.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This was observed in several studies, who found the lower implantation rate in high estradiol level condition during IVF ET cycle [10] [14] [15]. However, the difference in pregnancy results was not the primary goal of this study.…”
Section: Discussionmentioning
confidence: 51%
“…Kutlu et al conducted a study to evaluate whether the AUC of E2 might be used as a predictor of clinical pregnancy or implantation failure. They found that there was a significant difference between AUC of E2 in women with successful implantation and those whose implantation was failed [10]. They concluded that the AUC of E2 might be used for predicting implantation success.…”
Section: Discussionmentioning
confidence: 99%
“…18 In our previous publication, we showed the significant value of the degree of endometrial estrogen exposure to predict implantation failure. 19 All these data show us that premature progesterone increase is a secondary finding of hyperstimulation and the degrees of hyperstimulation and high E2 causing impaired endometrial receptivity are better predicted by AUCEM.…”
Section: Discussionmentioning
confidence: 89%
“…This role of P4 is important in the establishment of pregnancy through the promotion of endometrial receptivity of the blastocyst and attachment of the trophoblast by suppression of deleterious maternal immune responses [15, 16]. Studies have used the area under curve of temporal progesterone measurements (AUCPM) on the implantation of embryos and thus clinical pregnancy in assisted reproductive technology (ART) in women [1, 17]. Other studies have also used the quantity of P4 to predict the probability of pregnancy in cattle [1, 18].…”
Section: Introductionmentioning
confidence: 99%